Gestão de energia para a indústria frigorífica de aves: viabilidade técnica e econômica - Portela, Tarlis Tortelli (2015)
Energy is a strategic issue for industry, society, economy and national security. The efficiency and power management are in focus on a world stage. Several policies specially designed for energy efficiency, demand for renewable energy and cleaner production are in development. The literature shows little concrete information to promote commitment of organizations with such policies. Brazilian organizations are not well supported in this aspect, the country lacks a national policy that promotes efficient energy use. The chicken slaughterhouse industry has few information to compare its energy performance with others and often do not know the actions they can take. Nor they establish criteria for evaluating their performance and improvement goals. Comparing two local industries, shows performance 218.33% lower of one to the other for processing the same product. For that, the management of energy efficiency (EE) starts in performance evaluation through indicators. In this context, the development of these indicators and identification of technologies for monitoring EE conditions may enable these industries to establish energy baselines to compare its performance over time. The work also dedicates to specify a set of economic feasibility analysis tools of an EE monitoring system based on the proposed indicators in order to promote the adoption of energy management systems (EMS) by industries. Thus, investment analysis are required and EMS in medium slaughterhouse industries shows plausible investment return when generation of 5% savings in electricity costs are possible. However, good reliability in economic analysis of an EMS can be reached in case studies that consider the specific needs of each institution. And yet, the mere creation of an EE monitoring system is unable to generate savings, but other investments in improvements of industrial processes can. Finally, this paper aims to help industries develop their energy performance indicators and evaluating investments in the creation of EMS.